Comparative Characterization of Trends and Patterns of Physical and Chemical Attributes of Optimal and Traditional Processed Cowpea Leaves - Joshua Ombaka Owade; George Ooko Abong’; Michael Wandayi Okoth; Agnes Wakesho Mwang’ombe (Journal of Food Quality)
Seasonality in the availability of cowpea leaves has often limited their utilization and thus the promotion of preservation techniques that convert the vegetables into storable and stable forms. The recommendations for the use of highly mechanized techniques in preservation are brought into question due to limited affordability among resource-constrained households that prefer less costly approaches. Therefore, this study used statistical techniques of principal component analysis to comparatively evaluate the trends of physicochemical quality of the two diverse approaches of processing cowpea leaves. The study evaluated dehydrated cowpea leaves of different processing techniques from farmer groups and optimally processed using modern techniques for nutritional composition, phytochemical compounds, and colour changes. Sun drying techniques that excluded blanching had the least content of beta-carotene and ascorbic acid, 2.65 ± 0.95 and 21.80 ± 1.24 mg/100 g dry weight basis (dwb), respectively, accompanied by the most significant (p<0.001) deterioration of colour (7.74 ± 3.49) than techniques that included. Whereas the antinutrients declined, the difference did not significantly differ (p>0.05) based on preservation techniques. With factor analysis determining optimal nutritional quality for cowpea leaves at 8 weeks after emergence, sun drying had the highest loss of beta-carotene and ascorbic acid, 66.7–80.1% and 53.7%–58.3%, respectively (p<0.001), whereas mineral leaching, reduction of antinutrients, and colour changes were more pronounced in dehydration techniques incorporating fermentation as pretreatment. For the traditional preservation techniques, increasing retention of minerals resulted in aggravated losses of beta-carotene and ascorbic acid, whereas in the mechanized techniques, this was not the case. In concluding that the mechanized techniques have a better combination of attenuating losses of micronutrients, the study recommends that in promoting the utilization of traditional preservation techniques, low-cost processes like steam blanching can help improve the nutritional quality of the product.